2010 Second International Workshop on Education Technology and Computer Science 2010
DOI: 10.1109/etcs.2010.150
|View full text |Cite|
|
Sign up to set email alerts
|

Notice of Retraction: A Pattern for Training Students' Innovative Ability of Computer Science in Independent College

Abstract: The innovative ability is one of core targets of talents training scheme of colleges and universities. Most of independent colleges hven't been established more than a decade and the students of independent college are enrolled by the third batch of undergraduate enrollment. Because of the students lacking selflearning ability and study consciousness, most of the teachers lacking teaching experience, the investment in scientific research and laboratory facilities being inadequate, training students' innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It was clearly stated in the literature that new media is a sort of medium for education (Angela, 2011), and it is a requisite for teachers to integrate new media into instruction (Alvarez et al, 2013;Young, 2015). It is also clearly known that the successful integration of innovative technologies into education highly relies on the degree to which teachers accept and use them in their teaching practices, and consequently, teacher training has a key role in this respect (Bo & Ye-mei, 2010;Go¨kc¸earslan et al, 2017;Robertson, Macvean, & Howland, 2013). In this sense, the results of this study revealed that preservice teachers demonstrated the highest level of NML in FC followed by CC and FP while they had the lowest NML in CP.…”
Section: Discussionmentioning
confidence: 99%
“…It was clearly stated in the literature that new media is a sort of medium for education (Angela, 2011), and it is a requisite for teachers to integrate new media into instruction (Alvarez et al, 2013;Young, 2015). It is also clearly known that the successful integration of innovative technologies into education highly relies on the degree to which teachers accept and use them in their teaching practices, and consequently, teacher training has a key role in this respect (Bo & Ye-mei, 2010;Go¨kc¸earslan et al, 2017;Robertson, Macvean, & Howland, 2013). In this sense, the results of this study revealed that preservice teachers demonstrated the highest level of NML in FC followed by CC and FP while they had the lowest NML in CP.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers have a significant role in the efficient provision of content developed in a technological form (Southall, 2012). If it is thought that the level of innovation of preservice teachers will directly or indirectly affect the education they give, it will be understood that the studies made in this field are very important in terms of training more qualified teachers and generations (Bo & Ye-mei, 2010). According to this result, situations for improving the innovation of teacher and preservice teachers should be investigated (Bingimlas, 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Internet technologies, information and communication technologies have been developing and this development offers innovations to many fields including education (Lim & Ching, 2004;Richards, 2006;Sang, Valcke, Braak, &Tondeur, 2010). Teachers have important roles in adoption, learning, and transferring of these developing technologies (Bo & Ye-mei, 2010;Mandell, Sorge, & Russel, 2002). Training teachers applying different methods to increase the participation of students and putting into practice new abilities by changing their behaviors is important in terms of integration of developing technologies into education (Ritchhart, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is that there are following problems in the computer training. In the computer specialty of independent college, the training of talents is greatly paid attention to [1]. Most research is done in the training of the ability of students.…”
Section: Introductionmentioning
confidence: 99%